Serum biochemical profile of repeat breeder crossbred cows - CHANDRAHAR, DEEPAK; TIWARl, R P; AWASTHl, M K; DUTTA, G K (The Indian Journal of Animal Reproduction, 2023)
Glucose. inorganic phosphoru s, total protein. albumin , cholesterol and alkaline phosphatase were estimated in blood serum of repeat breeder crossbred cows and their levels were compared with that of normal fertile cows. The repeat breeder cows had significantly lower (P < 0.0 I) level of blood glucose and inorganic phosphorus while serum calcium, albumin and alkaline phosphatase were at significantly higher level (P < 0.01). The difference in total protein and serum cholesterol levels between two groups were non-significant.